2021
DOI: 10.1007/s11205-021-02747-y
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensionl Poverty and The Role of Social Capital in Poverty Alleviation Among Ethnic Groups in Rural Vietnam: A Multilevel Analysis

Abstract: This paper empirically examines the disparities over time across six dimensions of poverty (monetary, education, health, housing, basic services, and durable assets) between ethnic minority and majority households in rural Vietnam. Using the five-wave panel data of the Vietnam Access to Resources Household Survey (VARHS) 2008–2016, we observe improvements in most non-monetary dimensions of poverty for both ethnic groups, while the monetary dimension shows the highest degrees of deprivation and the lowest rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 119 publications
0
20
1
Order By: Relevance
“…Farmer households’ total social capital index has a positive and significant impact on credit through different channels. Therefore, it is confirmed once again that the influence of each dimension should be specifically analyzed when analyzing the influence of social capital on farmer households’ credit channels ( Pham and Mukhopadhaya, 2022 ).…”
Section: Discussionmentioning
confidence: 81%
“…Farmer households’ total social capital index has a positive and significant impact on credit through different channels. Therefore, it is confirmed once again that the influence of each dimension should be specifically analyzed when analyzing the influence of social capital on farmer households’ credit channels ( Pham and Mukhopadhaya, 2022 ).…”
Section: Discussionmentioning
confidence: 81%
“…Social capital is intangible and re ects the resources people can access to create value through interaction, cooperation and coordination (Priyanath and Lakshika, 2020;Tahmasebi and Askaribezayeh, 2021). Previous studies have found that social capital can alleviate poverty through various approaches, such as promoting resource sharing (Pham and Mukhopadhaya, 2021;Weber et al, 2013), decreasing information asymmetry (Hong and Tisdell, 2017), and lowering transaction costs (Harrison et al, 2019;Priyanath and Lakshika, 2020). Few studies concern migrant workers' social capital and poverty state.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Poverty level is the dependent variable in our study and is measured from the multidimensional perspective. Based on the MPI Questionnaire proposed by the Oxford Poverty and Human Development Initiative (OPHI), some scholars have developed multidimensional poverty indicators based on the living conditions in the target area (Chen et al, 2019;Pham and Mukhopadhaya, 2021), such as life quality, economic condition, abilities and development opportunities. Considering the migrant workers' characteristics, we measure migrant workers' multidimensional poverty level from three dimensions: economic status, abilities, and social inclusion.…”
Section: Scales and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…In Indonesia, it is more about business development through funding assistance, institutional strengthening, strengthening regional income, and education [9, 10,[19][20][21][11][12][13][14][15][16][17][18]. In Vietnam, it is more about developing human resources, and providing funding facilities [22][23][24][25][26][27]. In Philippines, focused on social relation and creating community support system [28], while in Malaysia it is more focused on IT [29].…”
Section: Table 2 Poverty Eradication Effortmentioning
confidence: 99%